Factors affecting the students’ English oral presentation skills at Hanoi Tourism College - Hoang, Thi Mai Hoa (University of Languages and International Studies, 2017)
The research is concerned with factors affecting students’ oral presentation skills in English at Hanoi Tourism College. Specifically, a survey is conducted on 106 third year tour guide students. Main purposes of the research are to find out: (1) the diffi (...)